EL DESARROLLO DEL BANANO Y LA PALMA ACEITERA EN EL PACÍFICO COSTARRICENSE DESDE LA PERSPECTIVA DE LA ECOLOGÍA HISTÓRICA - Clare, Patricia (2005)
From the perspective of Ecological History this article broaches the topic of the development of banana and oil palm plantations on the Costa Rican Pacific coast.